Любовная паутина: [роман] / Х. Флеминг - Флеминг Хлоя (Панорама романов о любви, 2005)
Экземпляры: ЧЗ (20181213) / Инвентарный номер: 44404 / Цена: 15 / Сис.шифр: 84(7) / Авт.знак: Ф 71 / ГРНТИ: 17.82 / ББК: 84(7Сое)